KONSELING KARIR DI ERA REMOTE WORK: TANTANGAN DAN STRATEGI ADAPTASI KONSELOR DALAM MEMFASILITASI PENGEMBANGAN KARIR - Sari, Siwi Vilia Intan; Amalia Cindi Andriani; Herfano Prabandaru (INSIGHT: Jurnal Bimbingan Konseling, 2025)
The transformation of the workplace toward remote work has fundamentally altered the career landscape and the need for career counseling services. These changes have significant implications for career counseling practice. This article examines the challenges faced by career counselors in the era of remote work and the adaptation strategies that can be implemented to facilitate clients' career development effectively. A literature review approach indicates that the challenges revolve around clients' social isolation, blurred work-life boundaries, unstructured career management, and the need for technological competency. Proposed adaptation strategies include developing counselors' digital competencies, integrating technology into counseling services, a holistic approach to career well-being, collaboration with digital stakeholders, and the use of approaches that highlight career flexibility and resilience. The study findings suggest that career counselors need to undertake a paradigm shift from traditional models to a more flexible and responsive approach to the dynamics of remote work to remain relevant and effective in facilitating career development in the digital era.